A novel dietary strategy to increase colonic propionate production in humans and improve appetite regulation and bodyweight management. Issue 3 (23rd August 2015) - Chambers, E. S.; Morrison, D. J.; Tedford, M. C.; Frost, G.
Abstract: A number of animal and human investigations have demonstrated that dietary supplementation with non‐digestible carbohydrates (NDC) improves appetite regulation and bodyweight. These positive metabolic effects have been linked to the elevated production of short chain fatty acids (SCFAs) through fermentation of NDC by the colonic microbiota. Of the principle SCFAs, propionate has the highest affinity for free fatty acid receptor 2 (FFAR2), which is expressed on colonic L‐cells and upon stimulation secretes anorectic hormones. Augmenting colonic propionate is therefore an attractive target to improve appetite regulation and, as part of the BBSRC DRINC initiative, we developed a novel dietary molecule, inulin‐propionate ester that we demonstrate increases colonic propionate levels in humans. Our further studies with inulin‐propionate ester in human volunteers suggest that dietary interventions that enhance colonic propionate levels may be a strategy to improve appetite regulation and weight management at the population level.